Advances in Information and Communication Technology Proceedings of the International Conference, ICTA 2016 - Akagi, Masato; Nguyen, Thanh-Thuy.; Vu, Duc-Thai.; Phung, Trung-Nghia.; Huynh, Van-Nam.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book features papers presented at the International Conference on Advances in Information and Communication Technology (ICTA 2016), which was held in Thai Nguyen city, Vietnam, from December 1 to 13, 2016. The conference was jointly organized by Thai Nguyen University of Information and Communication Technology (ICTU), the Institute of Information Technology - Vietnam Academy of Science and Technology (IoIT), Feng Chia University, Taiwan (FCU), the Japan Advanced Institute of Science and Technology (JAIST) and the National Chung Cheng University, Taiwan (CCU) with the aim of bringing together researchers, academics, practitioners and students to not only share research results and practical applications but also to foster collaboration in information and communication technology research and education. The book includes the 66 best peer-reviewed papers, selected from the 150 submissions received.
A New Neuro-fuzzy Inference System for Insurance Forecasting -- Swarm Intelligence-based Approach for Macroscopic Scale Odor Source Localization Using Multi-robot System -- Quality Improvement of Vietnamese HMM-based Speech Synthesis System Based on Decomposition of Naturalness and Intelligibility Using Non-negative Matrix Factorization -- Predicting Early Crop Production by Analysing Prior Environment Factors -- An Evolutionary-based Term Reduction Approach to Bilingual Clustering of Malay-English Corpora -- Estimation Localization in Wireless Sensor Network Based on Multi-Objective Grey Wolf Optimizer -- New Block Ciphers for Wireless Mobile Networks -- Managing Secure Personal Mobile Health Information -- Design Adaptive-CTC Controller for Tracking Target Used Mobile Robot-pan Tilt-stereo Camera System -- A Study on Fitness Representation in Genetic Programming -- Comparing Modified PSO Algorithms for MRS in Unknown Environment Exploration -- Toward Cyber Security Architecture Framework.>.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence